2017
DOI: 10.1016/j.bbrep.2017.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage ubiquitin-specific protease 2 modifies insulin sensitivity in obese mice

Abstract: We previously reported that ubiquitin-specific protease (USP) 2 in macrophages down-regulates genes associated with metabolic diseases, suggesting a putative anti-diabetic role for USP2 in macrophages. In this study, we evaluate this role at both cellular and individual levels. Isolated macrophages forcibly expressing Usp2a, a longer splicing variant of USP2, failed to modulate the insulin sensitivity of 3T3-L1 adipocytes. Similarly, macrophage-selective overexpression of Usp2a in mice (Usp2a transgenic mice) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…To further evaluate the anti-inflammatory properties of USP2A in macrophages, we employed a different macrophage model. We measured cytokine gene expression in macrophages isolated from Tg mice ectopically expressing Usp2a under the control of the FIRE promoter [ 24 , 29 ]. After treatment with LPS (5 μ g/mL) for 4 h, we measured the expression levels of cytokine transcripts in macrophages isolated from Usp2a Tg mice, as well as in littermate control mice.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To further evaluate the anti-inflammatory properties of USP2A in macrophages, we employed a different macrophage model. We measured cytokine gene expression in macrophages isolated from Tg mice ectopically expressing Usp2a under the control of the FIRE promoter [ 24 , 29 ]. After treatment with LPS (5 μ g/mL) for 4 h, we measured the expression levels of cytokine transcripts in macrophages isolated from Usp2a Tg mice, as well as in littermate control mice.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, Usp2a Tg mice exhibited minimal accumulation of USP2A proteins in their macrophages, although their Usp2a transcript levels had increased dramatically [ 29 ]. Small increases in USP2A protein levels may result in relatively weak expressional changes in metabolic disorder-associated genes in adipose tissue macrophages, followed by gradual changes in insulin sensitivity [ 24 ]. This implies that certain posttranscriptional or posttranslational mechanisms work to keep intracellular USP2 pools at a constant level in isolated macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Western blotting analysis was performed as previously described (Saito et al, ). Briefly, total cellular protein was extracted with RIPA buffer (50 mmol/L Tris‐HCl [pH 7.6], 150 mmol/L sodium chloride, 1% Nonidet P‐40, 0.5% sodium deoxycholate, 0.1% SDS, 1 mmol/L EDTA, protease inhibitor cocktail [Roche Life Science, Basel, Switzerland]).…”
Section: Methodsmentioning
confidence: 99%
“…USP2, a member of the USP family, is widely expressed in organs, with relatively higher expression levels reported in the testis and skeletal muscle (Gousseva and Baker, 2003;Kitamura et al, 2013). It has diverse functions in a wide variety of cells, such as pro-and antiapoptotic effects in cancerous cells (Gewies and Grimm, 2003;Priolo et al, 2006), regulatory roles in cytokine production in macrophages (Zhang et al, 2014;Sun et al, 2016;Kitamura et al, 2017), and modulation of glucose and lipid metabolism (Molusky et al, 2012;Kitamura et al, 2013;Nelson et al, 2016;Saito et al, 2017). In a previous study, dominant negative forms of USP2 were found to interrupt the differentiation of L6 myoblasts into myofibers indicating the involvement of USP2 in myocyte differentiation (Park et al, 2002).…”
Section: Introductionmentioning
confidence: 99%